2003
DOI: 10.1007/s10690-005-4246-7
|View full text |Cite
|
Sign up to set email alerts
|

Are Banks Affiliated with Bank Holding Companies More Efficient Than Independent Banks? The Recent Experience Regarding Japanese Regional BHCs

Abstract: Few studies have investigated whether Japanese banks affiliated with bank holding companies are more efficient and profitable than independent banks. The present paper tests this hypothesis by using both a stochastic frontier approach and a market valuation approach. First, our results suggest that banks affiliated with bank holding companies are not more cost-efficient than are independent banks. Because of the brief history of Japanese BHCs, it is fair to conclude that the formation of regional bank holding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Firstly, we focus on organizational forms of banks as these characteristics, because using data from Japanese regional banks, Yamori et al (2003) confirm that banks affiliated with BHC are more profit-efficient than independent banks. Yamori et al(2003) has suggested that that Japanese banks affiliated with bank holding companies (BHCs) are more profit-efficient than are independent banks. Therefore, it is possible that BHCs will implement revenue diversification derived from their activities in securities, insurance, and fiduciary business more efficiently than independent banking companies will.…”
Section: Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we focus on organizational forms of banks as these characteristics, because using data from Japanese regional banks, Yamori et al (2003) confirm that banks affiliated with BHC are more profit-efficient than independent banks. Yamori et al(2003) has suggested that that Japanese banks affiliated with bank holding companies (BHCs) are more profit-efficient than are independent banks. Therefore, it is possible that BHCs will implement revenue diversification derived from their activities in securities, insurance, and fiduciary business more efficiently than independent banking companies will.…”
Section: Specificationmentioning
confidence: 99%
“…In addition, we account for the possibility of non-linearity that the effects of revenue diversification on franchise value or risk measures are affected by organizational form of banks and their performances in traditional banking business, because it is considered that banks that perform well in traditional banking business can more effectively implement their revenue diversification than those banks that perform badly. In addition, Yamori et al (2003) confirm that Japanese banks affiliated with bank holding companies (BHCs) are more profit-efficient than are independent banks. Therefore, it is plausible that BHC organizations may implement revenue diversification more efficiently than do independent banking organizations.…”
Section: Introductionmentioning
confidence: 96%
“…Soft information is defined as information that is difficult to communicate in a 1 Amel, Barnes, Panetta, and Salleo [2004] and Berger, Demsetz, and Strahan [1999] provide concise literature reviews on this subject. 2 The literature along this line includes Cornnet, McNutt, and Tehranian [2004], Hosono, Sakai, and Tsuru [2006], Houston, James, and Ryngaert [2001], Humphrey and Vale [2004], Kane [2000], Knapp, Gart, and Becher [2005], Penas and Unall [2004], Rhodes [1998], Rime and Stiroh [2003], Stiroh [2000], Stiroh and Rumble [2006], and Yamori, Harimaya, and Kondo [2003]. 3 As for deposit interest rates, it is found that they temporarily go down after bank mergers (Prager and Hannan [1998]) but eventually go up as efficiency gains materialize in the long-run (Focarelli and Panetta [2003]).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous BHCs have also been established in Japan [8]. However, Yamori et al (2003) found that regional banks affiliated with BHCs are not more cost efficient than independent banks, while the issue of bank branch expansion is not investigated. To the best of our knowledge, very few studies have investigated the issue of branch networks in the context of Japanese banks.…”
Section: Introductionmentioning
confidence: 99%